Morphological and anatomical investigations in Desmodium tortuosum (Sw.) DC. (Fabaceae): A new addition to the Egyptian flora - Shaheen, Abdel Samai Moustafa (Bangladesh Journal of Plant Taxonomy, 2008)
The morphological, anatomical and micromorphological features of Desmodium tortuosum (Sw.) DC. were investigated to assist in the identification of the species as a new record for Egypt. Specimens collected from different places in the Egyptian Nubia (Nubian Nile Valley) confirmed the presence of D. tortuosum as a naturalized species in the country. In general, the results obtained from the morphological studies were consistent with the previous studies on this species. However, the present investigation into leaf, petiole and stem anatomy and the seed and the leaf patterns under light and scanning electron microscopes, respectively, is the first such study on the species. Keywords: Adaxial bundle, Abaxial bundle, Seed pattern, Micromorphology, Desmodium tortuosum DOI: 10.3329/bjpt.v15i1.908 Bangladesh J. Plant Taxon. 15(1): 21-29, 2008 (June)